The effect of flavonoids on the reduction of cupric ions, the copper-driven Fenton reaction and copper-triggered haemolysis - Lomozová, Zuzana; Hrubša, Marcel; Conte, Palma Federica; Papastefanaki, Eugenia; Moravcová, Monika; Catapano, Maria Carmen; Proietti Silvestri, Ilaria; Karlíčková, Jana; Kučera, Radim; Macáková, Kateřina; Mladěnka, Přemysl (Food chemistry, 2022)
Flavonoids are considered beneficial, but they may exhibit pro-oxidative effects likely due to metal reducing properties. For the first time, 24 structurally related flavonoids were compared for copper reduction, and modulation of the copper-triggered Fenton reaction and lysis of erythrocytes. The vast majority of flavonoids reduced cupric ions; their behaviour ranged from progressive gradual reduction through bell-shaped, neutral, to a blockade of spontaneous reduction. Similarly, different behaviours were observed with the Fenton reaction. Flavone was the only flavonoid that potentiated copper-triggered haemolysis (155 ± 81 % at twice the amount of Cu2+), while 18 flavonoids were at least partly protective in some concentrations. Only 5-hydroxyflavone did not reduce Cu2+ and behaved as an antioxidant in both assays (reduction of 60 ± 10 % and 88 ± 1%, respectively, at an equimolar ratio with Cu2+). In conclusion, relatively subtle structural differences resulted in very different anti/prooxidant behaviour depending on the model.
Keywords: hemolýza; Hemolysis; oxidace-redukce; Fenton reaction; antioxidancia; Hydroxyl radical; měď; ionty; Copper; Flavonoids; lidé; Ions; Oxidation-Reduction; Antioxidants; flavonoidy; Reduction; Humans